Totalisation/portability of social security benefits: Imperatives for global action - Anwarul Hoda; Durgesh Kumar Rai (Indian Council for Research on International Economic Relations (ICRIER), 2019)
The relative importance of migrant workers has been increasing in the world economy. Conscious of their growing numbers, the migrant-receiving and migrant sending countries have agreed to grant social security benefits to migrant workers and their families. To this end they have ratified or accepted ILO Conventions and Recommendations and also entered into multilateral and bilateral agreements. But significant gaps still remain in the social security protection of these workers around the world. In most countries, the realisation of long term social security benefits is subject to qualification requirements in terms of relatively long periods of contribution, employment or residence, which migrant workers find difficult to fulfil as they work in multiple jurisdictions during their life time. This study attempts to build a case for global action for improving the social security protection of international migrant workers. It identifies the critical gaps in social security protection for migrant workers in important countries, which are host to the majority of international migrant workers and draws up arguments for concerted action to close these gaps.
Keywords: F22; J32; J88; 330; portability; totalisation; social security benefits; migrant workers